Exchange Rate Volatility and Tourism Receipts in Nepal: Evidence from GARCH Models - Adhikari, Gyan Mani; Chalise, Mahananda; Adhikari, Rajendra; Chhetri, Santosh; Shreshtha, Jamuna (Journal of Tourism & Adventure, 2025)
This study investigates the relationship between exchange rate volatility and tourism receipts, utilizing annual data from 1976 to 2024. While prior studies have focused on multiple determinants of tourism demand, the relationship between exchange rate volatility and tourism receipts has received minimal attention. The literature thus provides policymakers with limited guidance regarding how exchange rate fluctuations impact tourism revenue. Using time series data and various GARCH modeling approaches (standard GARCH, EGARCH, and TGARCH), we find strong evidence that exchange rate movements have a significant impact on tourism receipts. We found that exchange rate changes have a statistically significant impact on tourism receipts across all model specifications, with the EGARCH model showing the best fit based on information criteria. One possible explanation is that currency depreciation leads to improved price competitiveness, which can be an important driver of tourism revenue if properly leveraged through targeted marketing strategies.